DEGLACIAL METHANE EMISSION SIGNALS IN THE CARBON ISOTOPIC RECORD OF LAKE BAIKAL - Prokopenko A.A.; Williams D.F. (My University, 2004)
Changes in the concentrations of atmospheric greenhouse gases constitute an important part of global climate forcing. Here we present the first continental evidence for climatically caused changes in a methane gas hydrate reservoir. The organic carbon stable isotope record from Lake Baikal during the past 130 000 years registers regular emissions of isotopically light carbon by the occurrence of distinct negative shifts of 3–5‰ at every major orbitally forced cold-to-warm climatic transition during the past 130 000 years, including marine oxygen isotope stage boundaries 6/5e, 5d/5c, 5b/5a and 2/1. We conclude that these emissions were associated with decomposition of sedimentary clathrates, widespread in the Baikal basin. Among potential hypotheses to account for these methane episodes, the most probable appears to be hydrate dissociation due to deglacial warming of lake water. We estimate that as much as 12–33 Tg of methane could have been released with each episode. By recording the systematically recurring episodes of massive methane clathrate decomposition closely linked with the northern hemisphere temperatures during major orbital warmings, the new Baikal δ13C record provides further evidence for the potential involvement of clathrate reservoir in rapid deglacial rises of atmospheric methane levels.